Pengembangan pendidikan teknologi dan kejuruan dan hubungan dunia kerja - Nizwardi Jalinus (Jurnal Pendidikan Vokasi, 2011)
DEVELOPMENT OF TECHNOLOGY AND VOCATIONAL EDUCATION AND WORK WORLD RELATIONSBased on universal issues in the era of globalization, this article describes some phenomena how essential the role of Vocational and technical education in recent year to support the development of work forces in Indonesia. The wise government policies are needed to run various program of Vocational and technical educationin entire country, which is based on world-work needs. The common problem appeared is how to build the "mutual symbiotic" relationship between vocational and technical schools and the world of work.